Income inequality in today’s China - Xie, Yu; Zhou, Xiang (Proceedings of the National Academy of Sciences - PNAS, 2014)
Using multiple data sources, we establish that China's income inequality since 2005 has reached very high levels, with the Gini coefficient in the range of 0.53–0.55. Analyzing comparable survey data collected in 2010 in China and the United States, we examine social determinants that help explain China’s high income inequality. Our results indicate that a substantial part of China’s high income inequality is due to regional disparities and the rural-urban gap. The contributions of these two structural forces are particularly strong in China, but they play a negligible role in generating the overall income inequality in the United States, where individual-level and family-level income determinants, such as family structure and race/ethnicity, play a much larger role.